STRATEGIES FOR DEVELOPING MANGROVE ECOTOURISM IN RIAU PROVINCE, INDONESIA - Musadad Musadad; Mariaty Ibrahim Ibrahim (Institut Pariwisata dan Bisnis Internasional, 2019)
Mengkapan Mangrove Ecotourism, located in Siak Regency, Riau Province, was once visited by a large number of visitors soon after it was opened for public in 2015. Nevertheless, since the beginning of 2016, the number of visitors has been drastically dropped. One of the causes of this unfortunate condition is that there is no established planning to guide the development of the mangrove ecotourism. Therefore, this study was aimed to formulate strategies for developing the Mengkapan Mangrove Ecotourism by using the SWOT analysis. The data was collected through conducting interviews with related stakeholders, distributing questionnaires to them, and performing field observations. The collected data was then analyzed inductively to capture the key strategy alternatives. Based on the results of SPACE Matrix and SWOT Matrix, this study formulates the following priority strategies: diversifying tourist attractions and promoting them massively by using online media, creating tour packages, and making a cooperation with travel agents.